A biomechanical study of relationship between sternum defect patterns and thoracic respiration. Issue 1 (1st January 2016) - Nagasao, Tomohisa; Kasai, Shogo; Shimizu, Yusuke; Sakamoto, Yoshiaki; Hatano, Asako; Morotomi, Tadaaki; Ogata, Hisao; Kishi, Kazuo
Abstract: Background : Various types of sternum defects are produced after the removal of thoracic tumors involving the sternum. The present study aims to elucidate the relationship between the defect patterns and their effects on thoracic respiration. Methods : Ten sets of finite element models were produced simulating thoraces of 10 persons and termed normal models. With each of the 10 normal models, the sternum was removed in six different ways to produce new models termed defect models. Defect models were categorized into hemi-superior (H-S), hemi-inferior (H-I), hemi-whole length (H-W), bilateral-superior (B-S), bilateral-inferior (B-I), and bilateral-whole length (B-W) defect types, depending on the locations of the defects. Respiratory movement was dynamically simulated with these models. The volume change the thoraces present during respiration was measured to evaluate the effectiveness of thoracic respiration. This value – defined as Δ V – was calculated and was compared between normal and defect models. Results : With H-W and B-W type models, Δ V dropped to around 20% of normal values. With H-S and B-S type models, Δ V dropped to around 50% of normal values. With H-I and B-I type models, Δ V presented values almost equivalent to those of normal models. Conclusion : Effectiveness of thoracic respiration is seriously impaired when the whole length of the sternum is absent. Reconstruction of the defect is essential for these cases. However, since the upper part of the sternum is most important for effective thoracic respiration, priority should be placed on the upper part in performing reconstruction.